Polyphenols targeting multiple molecular targets and pathways for the treatment of vitiligo - Yang, Yixuan; Du, Yanyuan; Cui, Bingnan (Frontiers in Immunology, 2024)
Vitiligo, a pigmentary autoimmune disorder, is marked by the selective loss of melanocytes in the skin, leading to the appearance of depigmented patches. The principal pathological mechanism is the melanocyte destruction mediated by CD8+ T cells, modulated by oxidative stress and immune dysregulation. Vitiligo affects both physical health and psychological well-being, diminishing the quality of life. Polyphenols, naturally occurring compounds with diverse pharmacological properties, including antioxidant and anti-inflammatory activities, have demonstrated efficacy in managing various dermatological conditions through multiple pathways. This review provides a comprehensive analysis of vitiligo and the therapeutic potential of natural polyphenolic compounds. We examine the roles of various polyphenols in vitiligo management through antioxidant and immunomodulatory effects, melanogenesis promotion, and apoptosis reduction. The review underscores the need for further investigation into the precise molecular mechanisms of these compounds in vitiligo treatment and the exploration of their combination with current therapies to augment therapeutic outcomes.